FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN UPAYA PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) PADA IBU RUMAH TANGGA DI KELURAHAN KRAMAS KOTA SEMARANG - Istiqomah, Istiqomah; BM, Syamsulhuda; Husodo, Besar Tirto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dengue Hemorrhagic Fever (DHF) is a vector-based diseases are a public health problem in Indonesia. DHF cases in district Tembalang reached 343 cases and most cases (13 cases) occured in Kramas area in 2015. Community behavior is very important for DHF. This study aims to determine the factors associated with the practice in the prevention of dengue fever in Kramas area Semarang City. Type of this research is analytical descriptive with cross-sectional study. The population are 800 housewife. The sample are 90 housewife were taken using random sampling technique. Data analysis using univariate and bivariat analysis with Chi Square test (significance level 0,05). The result showed that most of respondents is good knowledge (55,6%), supporting attitude (56,7), high perceptions (72,2%), abilibity rules (86,7), facilities and infrastructure available well (74,4%) good support from health workers (82,2%) good support from community leaders (74,4%), good support from family (68,9%). Variable are associated with preventive behaviour of DHF is attitude (p=0,005) facilities and infrastructure (0,003) and support from community leaders (0,002).